Diabetes mellitus gestacional : alterações histopatológicas em placentas humanas - Santos, José Ronaldo Alves dos (2016)
Diabetes Mellitus is a problem of global public health. It is estimated that there are over 171 million people with diabetes worldwide, and projections of the World Health Organization for 2030 suggest that the number could reach 366 million people. Thus, the aim of this study was to determine the histopathological changes in human placentas, and to describe the clinical conditions of parturien-tes diagnosed with or without Gestational Diabetes Mellitus and their newborns, there was therefore a histopathology and descriptive, pregnant women (n = 16 / group) met the authorized period from June 2015 to February 2016 at the Maternity Our Lady of Lourdes. Placentas of microscopy analysis was performed derived from pregnant women in normal placentas and conditions of pregnant women in hyperglycemic conditions, as well as analyzed the clinical conditions of these mothers. Among the maternal variables, the average weight of pregnant women showed different about the normoglycemic (73.0 kg ± 16.5) and gestational diabetes (79.0 kg ± 16.8). The mean gestational weeks showed different groups, (37,7 ± 3,37 weeks) for the group and normoglycemic (36,6 ± 1,62 weeks) for parturrientes gestational diabetes. When analyzing fetal variables, height of newborns showed different about the normoglycemic patients (49.0 cm ± 2.40) and gestational diabetes 45.8 cm ± 5.08), followed by thoracic perimeter , which was observed in normoglycemic (34.0 ± 1.69 cm) and the gestational diabetes (32.6 cm ± 1.16) respectively. It was found by assessing placental var-iables as the size of the placenta normoglycemic pregnant women was significantly higher (64.3 cm ± 9.53) when compared to gestational diabetic women (60.3 ± 11.3 cm). It was also observed as compared to the weight of the placentas of normoglycemic mothers (0.74 g ± 0.11) when compared to gestational diabetes (0.64 ± 0.16 g). The histopathological analysis showed that there was blades structural differences between the normoglycemic groups and gestational di-abetes. Having been observed that for the groups obtained in the period of 9 months were certain significant relationships between some variables, it suggests the continuity of research for a long time with more mothers to be able to relate more strikingly related factors placental changes influenced by hyperglycaemia and the pathogenesis of the disease and its relationship with maternal-fetal aggravating.